Employing virtual reality-enhanced task-based language learning and teaching to mitigate interview anxiety - Nik Aloesnita, Nik Mohd Alwi; Wan Noor Farah, Wan Shamsuddin; Umi Kalsom, Masrom; Sa, Nguyen Truong (Pacific Association for Computer Assisted Language Learning (PacCALL), 2025)
One of the main essences of task-based language learning and teaching (TBLT) is performing real-world and authentic tasks. This study investigates the potential of virtual reality (VR) as the medium to reinforce TBLT to stimulate authentic and real-world tasks to promote language learning. The present study's objective is to use a VR application called /spiːx/, designed to reduce learners’ anxiety in job interview settings. Fifty undergraduate learners from engineering, technical, and sciences enrolled in Professional Communication classes were recruited to participate in the study. Their interview anxiety was measured before and after three sessions of using /spiːx/. The findings reported a reduction in interview anxiety by 12%. A paired two-sample for means t-test was conducted, indicating a significant difference between the pre- and post-tests with a p-value of <0.05. The study suggests the potential of using VR in TBLT classrooms, which elevates interview learning experiences for the learners, especially for those with zero interview experience. The integration of VR through task-based learning could equip learners to navigate real job interviews more effectively and enhance their employability.